Analisis Keakuratan Indikator Bollinger Bands Terhadap Pergerakan Harga Saham: Studi Kasus pada Saham PT Astra Agro Lestari Tbk - Frankandinata, Frankandinata; Cahyadi, Yoyo (Bina Nusantara University, 2014)
Technical analysis is an analytical tool to analyze price movement of an investment instrument like stock. Practically, there are a lot of indicators that can be used in technical analysis. One of them is Bolinger Bands. Bolinger Bands has 3 moving averages lines, which are Upper Band, Middle Band, and Lower Band. Study used library research and software review by analyzing the candlestick chart of stock price with ChartNexus software. The stock for this study was Astra Agro Lestari (AALI) and the period was 1 July 2010 until 31 May 2013. Results showed that Bolinger Bands gave 45 signals in the period with 75.56% accuracy.